Public expenditure and institutional review: Ghana’s ministry of food and agriculture - Kolavalli, Shashidhara; Birner, Regina; Benin, Samuel; Horowitz, Leah; Asenso-Okyere, Kwadwo; Thompson, Nii Moi; Poku, John; Babu, Suresh Chandra (International Food Policy Research Institute, 2009)
Agriculture has been the backbone of a Ghanaian economy that has recorded positive per capita GDP growth over the last 20 years. The agriculture sector has grown rapidly at an average annual rate of 5.5 percent in recent years, benefiting from favorable weather conditions and world market prices for cocoa. However, growth patterns have been erratic over a longer period. Agricultural performance has not been uniform within subsectors and regionally: forestry and cocoa subsectors grew at double digit rates, while crops other than cocoa grew at rates ranging from 1.5 to 4.5 percent between 1991 and 2005. The high rate of expansion achieved in recent years may be difficult to sustain, as growth hasbeen led by extensive forces. Land expansion contributed more than yield increases to growth of various crops. Yields of most crops have not increased significantly. The level of adoption of agricultural technologies is also still low in the country. Reaching the productivity targets that the country has set for different crops will require rates of growth in productivity that are far higher than what have been achieved in the past (Breisinger et al. 2008). In leading the sector, the Ministry of Food and Agriculture (MoFA) has revised its Food and Agriculture Sector Development policy (FASDEP) through broad consultation. The policies of the ministry, its financial management, and the organizational capabilities to implement FASDEP II have become more important than ever, as the activities of the Ministry are increasingly financed through budget support. There are concerns that the Ministry may not have the capacity to effectively implement the policies and strategies that have been developed recently, since in the past budget support to the Ministry has not had the envisaged impact. A thorough understanding of the public expenditure environment in the Ministry is needed to develop effective strategies to strengthen its capabilities. Past studies of the Ministry have focused on either expenditure management or organizational issues dealing largely with management of and adjustment to structural changes such as decentralization. They have not considered whether linking expenditures, processes, and outcomes could improve effectiveness. Hence, there is a need to examine the internal processes relating to these two issues.